Duration of of Low-Temperature Storage, Clove Topping and Gibberellic Acid on Emergence, Yield and Yield Components of Garlic. (24th March 2022) - Desta, Bizuayehu; Woldetsadik, Kebede; Mohammed, Wassu; Tena, Netsanet
Abstract : Dormancy of freshly harvested garlic cloves does not allow early emergence, and preplanting garlic clove treatment is critical for more than one cycle of production in a year. This field experiment was conducted to assess the effect of treating cloves on emergence, growth, and yield of "Tseday" variety during the main cropping season of 2014/2015 and off-season of 2015/16 at Haramaya University. The experiment was arranged in a factorial combination of four (cold stored at 7°C for the duration of 10, 20, and 30 days and stored at room temperature 21°C for 30 days as control), two (whole and topped clove), and four GA3 treatment at concentration of 0, 125, 250, and 375 mg/l and distilled water treatment as second control laid out in randomized complete block design with three replications. The three main factors (clove type, cold storage duration, and GA3 ) and growing season showed significant influence on phenology, growth, bulb yield and yield components, and all size categories of cloves, while GA3 showed nonsignificant effect on days to emergence of cloves. Clove type interacted with cold storage duration and GA3, and cold storage duration interacted with GA3 significantly to influence all characters of the variety. In addition, the growing season also interacted with clove type and GA3 to influence all categories of clove size, bulb diameter, average bulb weight, and total bulb yield. The three main factors (clove type × cold storage duration × GA3 ) interaction significantly influenced all characteristics of the variety. However, 30 days of cold-stored and topped cloves reduced dormancy period and days to maturity by 18.84 and 19.50 days, respectively, and increased total bulb yield by 70.32% as compared to the control treatment. In addition, this treatment combination significantly increased most of the growth and bulb yield components, while the number and weight of small-sized cloves were decreased. Hence, it can be concluded that 30 days of cold storage and topping of cloves without soaking under GA3 could be recommended to enhance early emergence, good vegetative growth, and total bulb yield of the garlic variety both under rain-fed and irrigated conditions.